LEBER HEREDITARY OPTIC NEUROPATHY GENOTYPE, PHENOTYPE, AND BIOCHEMICAL CHARACTERISTICS - Petrović Pajić, Sanja (Medicinski podmladak, 2023)
Leber hereditary optic neuropathy (LHON) is a mitochondrial neurodegenerative disease presented as a painless, acute or subacute, usually sequential, loss of central visual acuity. The other eye is typically affected in a few weeks or months (on average in 6 to 8 weeks), while in about 25% of cases, the disease is simultaneously bilateral. Although individual unilateral cases have been reported, in 97% of cases, both eyes are affected within a year. Detailed genetic analysis is crucial in the process of diagnosing LHON. Between 75 - 90% of all the recorded LHON cases occur due to one of the three common mutations in mitochondrial DNA (mtDNA), located on nucleotides 11778, 14484, and 3460, although other, rare mutations with familial occurrence have been associated with LOHN as well. More recently, the so-called autosomal recessive LHON has been described, which occurs due to a mutation in the DNAJC30 gene and presents with identical clinical features, but a better visual prognosis compared to mtLHON. This short review aims to present relevant information on the phenotype, genotype, and biochemical characteristics of LHON.